Las ventanillas de Allpas, Acobamba ( Huancavelica) the Allpas ventanillas, Acobamba ( Huancavelica) - Ruiz Entrada, Arturo (2009)
The present research tries to approach the knowledge of the funerary complex of Allpas, located in the province of Acobamba (Huancavelica). It presents a particular form of graves which have been denominated «ventanillas» (usually small, window-like structures) due to its constructive pattern presenting cavities located at rocky cliffs. What is striking is the presence of this type of tombs in the region of Huancavelica, because they are considered to be typical of the Cajamarca region and what is even stranger is their time location and dispersion over long distances. Therefore, this is an attempt to offer some contributions pertaining to the knowledge of their nature, structure and chronology.